Nasal insertion depths for neonatal intubation. Issue 6 (22nd June 2020) - Maiwald, Christian Achim; Neuberger, Patrick; Mueller-Hansen, Ingo; Goelz, Rangmar; Michel, Jörg; Esser, Michael; Engel, Corinna; Franz, Axel R; Poets, Christian F
Abstract : Aim: Data on the depth of nasal intubation in neonates are rare, although this is the preferred route in some countries. Therefore, recommendations on optimal nasal intubation depths based on gestational age (GA) and weight are desirable. Methods: We determined the distances between the middle of thoracic vertebrae 2 (T2) and the tip of the endotracheal tube in 116 X-rays from nasally intubated neonates. The intubation depth (tip to nostril distance) that was documented in the digital patient's file was then corrected for this distance to reach an optimal nasal insertion depth. Results were plotted against the infant's GA and weight. Results: GA-based and birthweight-based charts and formulas for the nasal intubation depth in infants with a GA between 24 and 43 weeks and body weight between 400 and 4500 g were created. Conclusions: Generated data may help in predicting optimal insertion depths for nasal intubation in neonates.